2022
DOI: 10.3389/fphar.2022.989664
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor (TLRs) agonists and antagonists for COVID-19 treatments

Abstract: Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) rapidly infects humans and animals which make coronavirus disease 2019 (COVID-19) a grievous epidemic worldwide which broke out in 2020. According to data analysis of the other coronavirus family, for instance severe acute respiratory syndrome SARS coronavirus (SARS-CoV), can provide experience for the mutation of SARS-CoV-2 and the prevention and treatment of COVID-19. Toll-like receptors (TLRs) as a pattern recognition receptor (PRRs), have an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 147 publications
2
21
0
Order By: Relevance
“…Their therapeutic use is expected as well, considering the important function played by the molecules in the TLR pathway in the innate immune system; however, this is probably because immune cells and/or cancer cells activate distinct TLRs and downstream signaling cascades; alternatively, because of the temporal sequence of TLR activation in cancer cells or immune cells, studies on the role of TLR antagonists and agonists in inflammation and even cancer have been controversial (Table 2 ). 41 , 321 , 322 , 323 …”
Section: Clinical Therapy Involving Tlrsmentioning
confidence: 99%
“…Their therapeutic use is expected as well, considering the important function played by the molecules in the TLR pathway in the innate immune system; however, this is probably because immune cells and/or cancer cells activate distinct TLRs and downstream signaling cascades; alternatively, because of the temporal sequence of TLR activation in cancer cells or immune cells, studies on the role of TLR antagonists and agonists in inflammation and even cancer have been controversial (Table 2 ). 41 , 321 , 322 , 323 …”
Section: Clinical Therapy Involving Tlrsmentioning
confidence: 99%
“…IL-6 antagonists such as Tocluzimab and IL-6 inhibitors such as Chloroquine were also shown to be efficient in the treatment of CS associated with virus diseases (multicenter collaboration group of Department of, Technology of Guangdong, and Health Commission of Guangdong Province for chloroquine in the treatment of novel coronavirus 2020 ; Tanaka et al, 2016 ). TLR agonists and antagonists were also shown to have therapeutic potential against CS associated with RNA virus infection ( Liu et al, 2022 ).…”
Section: Potential Therapeutics For Cs Treatment and Associated Chall...mentioning
confidence: 99%
“…Therefore, targeting PRRs and related pathways could attenuate the hyperactivation of immune response and reduce cytokine storm. Indeed, several studies have demonstrated that PRR antagonists have beneficial roles and might be used as potential therapeutic drugs for COVID-19, though the exact dosage and duration should be carefully evaluated and tested before clinical use [ 141 , 142 , 143 ]. Timing is crucial for effective treatment against inflammation caused by viral infection [ 144 ].…”
Section: Potential Use Of Protein Adjuvant and Therapeuticsmentioning
confidence: 99%